Dampak Penggunaan Instagram sebagai Media Pencitraan pada Kalangan Remaja di Palembang - Ali Ibrahim; Dea Tri Ananda; Fadilah Nur Imani; St Dhiah Raniah Napian (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2019)
The rapid development of technology in this era has affected the development of communication technology. Most People in this era communicate through an online platform. Social media is a communication technology that utilizes the advanced development of technology. It has a variety of types depending on the features offered, for example, Instagram social media that offers a photo upload feature. Instagram is one of the most famous social media, because of its superiority which can display photo along with the description sentence which is known as caption. This feature distinguishes Instagram from other social media. The rise of the use of Instagram has encouraged us to conduct research on the Impact of Using Instagram as a Self-branding Media for Teenagers in Palembang City. The study was conducted using explanative research methods with data collected through observation and distribution of questionnaires conducted in two places, SMAN 11 and SMA Muhammadiyah 1 Palembang. The questionnaire was distributed to 150 teen respondents with ages ranging from 14 to 18 years. Through this research, it was found that the use of Instagram as self-branding media among teenagers in Palembang city had an impact. It has positive and negative impacts. The positive impact is that it can motivate teenagers to upload useful posts, for example, uploads about their achievements and the beneficial activities they lead. However, the research also shows the negative impact of using Instagram as a Teenage Imaging media, namely the emergence of envy towards the ownership or achievements of their peers.